THE INFLUENCE OF INTENTION FINTECH USAGE ON ISLAMIC FINANCIAL INCLUSION IN INDONESIA WITH EXTENDED UTAUT THEORY - Abdul Aziz Idham; Rininta Nurrachmi; Wahyu Dwi Agung (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2026)
Despite the rapid growth of digital transactions in Indonesia, Islamic financial inclusion remains disproportionately low compared to the Muslim population size. There is a lack of comprehensive understanding regarding how religious values interact with modern technology acceptance models in the Shariah fintech landscape. Previous studies have extensively used UTAUT and UTAUT2 to measure general fintech adoption, but few have integrated "Religious Commitment" as a mediating variable alongside "Privacy Enablers" and "Inhibitors" specifically within the Indonesian Islamic financial inclusion context. This study aims to evaluate the determinants of Islamic fintech adoption by extending the UTAUT model with Religious Commitment as a mediator and examining the impact of privacy factors on behavioral intention. A quantitative approach was employed using purposive sampling of 100 Muslim respondents in Indonesia. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) via SmartPLS 4, evaluating both direct and indirect mediating effects. The results indicate that Performance Expectancy significantly dictates adoption through religious mediation. Interestingly, Effort Expectancy and Social Influence showed a negative path through religious commitment, suggesting that highly religious users prioritize Shariah compliance over mere ease of use or social trends. Religious Commitment is a "Key Success Factor" in mediating technology acceptance. Performance Expectancy and Privacy Enablers positively influence intention, while Religious Commitment acts as a filter that determines whether a technology is culturally and spiritually acceptable for Indonesian Muslims.